Digitizing the Product Catalog at Blimbingsari Creative Craft to Expand its Promotional Network: Digitalisasi Katalog Produk di Blimbingsari Creative Craft untuk Memperluas Jejaring Promosi - Bachtiar, Riza Rahimi; Purwaningtyas, Ayu; Yusuf, Dianni; Nur Hanif, Muhamad; Joko, Mohamad; Susanto, Eko Bagus (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
Banyuwangi has immense potential in terms of natural tourism and cultural heritage, which greatly attracts both domestic and international tourists. This presents an opportunity for Banyuwangi's souvenir businesses to continuously develop their enterprises. Blimbingsari Creative Craft (BCC) is one of UMKM in the craft industry, established in 2003. Its products have been marketed internationally, and BCC frequently receives financial support from the government to expand its business. Although BCC has already reached international customers, it currently lacks a website to showcase its company profile and products. The Community Service Program (PKM) conducted by lecturers and students from Politeknik Negeri Banyuwangi focuses on building a website to manage information on activities and product catalog. The program also includes training for BCC staff to manage data, ensuring that the displayed information is always up-to-date and available in real-time. The outcome of this project is a web-based platform with bilingual features, serving as a digital promotional tool for BCC's products. BCC staff expressed that the website has greatly facilitated the management of information and product catalog, making it easier to organize and store the data in a database